KEDUDUKAN WANITA DALAM MASYARAKAT TIONGKOK KUNO: STUDI KASUS FILM MULAN - Yusuf Arifin, Yohan (Santhet (Jurnal Sejarah Pendidikan Dan Humaniora), 2024)
The position of women in the structure of ancient Chinese society is very interesting to discuss, this is because traditions in China prioritized the position of men in all aspects of life in Chinese society at that time. This research uses Mulan movie as a research object to explain the position of women in ancient Chinese society. This research is a qualitative descriptive study that uses Mulan movie as reference material and is supported by other references related to the topic of this research. From the research results, it was found that the position of women in the life of ancient Chinese society was quite low, this was because there were many things that cornered women at that time, and also the discrimination they experienced where men were given priority over women. It is hoped that this research can provide additional references for those who wish to study Chinese culture and history, especially the position of women in ancient Chinese society.